2021
DOI: 10.1016/j.heliyon.2021.e08491
|View full text |Cite
|
Sign up to set email alerts
|

Hyperleptinemia results in systemic inflammation and the exacerbation of ischemia-reperfusion myocardial injury

Abstract: Aim Hyperleptinemia potentiates the effects of many atherogenic factors, such as inflammation, platelet aggregation, migration, hypertrophy, proliferation of vascular smooth muscle cells, and endothelial cell dysfunction. The present study analysed the effects of long-term hyperleptinemia in an in vivo myocardial ischemia-reperfusion model to demonstrate whether the in vivo deleterious effect also affects cardiac structure and function. Main methods Rats were subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
7
0
2
Order By: Relevance
“…It is known that hyperleptinemia in human and animals, including rats, leads to an increase in blood pressure, myocardial hypertrophy, impaired left ventricular function, and arrhythmias [ 12 , 39 , 40 , 41 ]. Previous studies showed that leptin directly depresses ventricular cardiomyocyte contraction through mechanisms related to NO-, JAK-STAT-, and MAPK-signaling pathways [ 13 , 22 , 23 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that hyperleptinemia in human and animals, including rats, leads to an increase in blood pressure, myocardial hypertrophy, impaired left ventricular function, and arrhythmias [ 12 , 39 , 40 , 41 ]. Previous studies showed that leptin directly depresses ventricular cardiomyocyte contraction through mechanisms related to NO-, JAK-STAT-, and MAPK-signaling pathways [ 13 , 22 , 23 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low nanomolar levels of leptin below 10 ng/mL (<1 nM) in rat blood plasma are considered as the physiological range [ 57 ]. Previously, we showed that leptin plasma concentrations in intact male Wistar rats aged 11–12 weeks was 3.0–4.0 ng/mL [ 41 ]. A recent study demonstrated that plasma leptin levels do not reflect cardiac leptin synthesis in the myocardium and may not predict leptin-related cardiovascular morbidity [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…[43] The relationship between leptin and cholesterol was also demonstrated in an animal study where rats had significantly higher total cholesterol levels after being injected subcutaneously with leptin for 8 days. [44] Triglycerides (TG) are another important component of blood lipids, and increased TG levels have been an independent risk factor for AS. [45] Leptin stimulates hepatic secretion of TG via the brain-vagus-hepatic axis.…”
Section: Effect Of Leptin On Risk Factors For Asmentioning
confidence: 99%
“…Studies in pregnant rodents have elegantly demonstrated the relationship between leptin and other atherogenic factors that are thought to promote inflammation, ischemia, and endothelial dysfunction, all of which are key features of PE [ 34 ]. The subcutaneous administration of leptin to pregnant rats resulted in adverse outcomes such as increased blood pressure, dyslipidemia, endothelial cell dysfunction, and overall increased markers of systemic inflammation [ 34 ].…”
Section: Mechanistic Insights From Animal Models Of Pementioning
confidence: 99%